2-Azaanthracenes: a chronology of synthetic approaches and bright prospects for practical applications. (3rd July 2019) - Taniya, Olga S.; Kopchuk, Dmitry S.; Khasanov, Albert F.; Kovalev, Igor S.; Santra, Sougata; Rahman, Matiur; Zyryanov, Grigory V.; Majee, Adinath; Charushin, Valery N.; Chupakhin, Oleg N.
Abstract : This review aims to summarize the common synthetic approaches towards 2-azaanthracenes in chronological order, as well as systematize information on the areas of application of 2-azaanthracenes. Abstract : 2-Azaanthracene(benzo[ g ]isoquinoline) is the second most common nitrogenous derivative of anthracene after acridine (2, 3-benzoquinoline, 9-azaanthracene). The introduction of the nitrogen atom into the aromatic core of this molecule allowed it to significantly push the boundaries of the application fields of 2-azaanthracene and its derivatives, compared to regular anthracene. This review aims to summarize the common synthetic approaches towards 2-azaanthracenes in chronological order, as well as systematize information on the areas of application of 2-azaanthracenes. In particular, emphasis is placed on the description of the 2-azaanthracene family as unique fluorophores and chromophores for creating modern cell stains, chemosensors, pH-probes, etc. In addition to regular 2-azaanthracene, the common methods for the synthesis of fused 2-azaanthracene as promising OLED components or as ligands for metal cations are reported.